Perancangan dan Pembuatan Kunci Pintu Rumah Menggunakan RFID Dengan Multi Reader Berbasis Arduino - Hermawan, Indra, Heru Supriyono, ST, MT, Ph.D, Dr. Ratnasari Nur Rohmah, ST, MT (2016)
A safe and comfortable home is the dream of everyone. Home security is of great concern to every homeowner. Home security systems typically rely on a conventional key. However, the conventional house key shape is easily duplicated. The use of Radio Frequency Identification (RFID) is suitable to replace the conventional security. Due to the RFID tag to be used as a substitute for conventional key has a unique ID that is different, so it can not be duplicated. There are other shortcomings of the use of RFID, as if this tag bias used by anyone. The purpose of this study is to add to and complement the key in the door lock with RFID in order to produce a high security for home security. In this study, two RFID reader is used to read data on tags. The use of two reader meant that in addition to tag ID, the key is also controlled by a unique code that is a pattern with two reader reading the tag. The tool is also equipped with a 16x2 LCD and LED RGB is used as an indicator of the viewer. Micro servo is a mechanical part of these tools, micro servo will be active when the command of the system. Users can use this door locking device in a way closer to the RFID tag reader each, with specific reading patterns. If UID dank same ode to the database, the system will activate the servo. The test is done to look at the accuracy of readers, a maximum reading distance of each reader, precision lock system works, speed reader when reading the pattern. From the test results showed that the reader is able to read well ID on the tag. Reader has a maximum distance range of readings 3,3cm. The accuracy of key systems such as UID and patterns of working 100%, system will only respond if the pattern readout according to the database, users will only be allowed to enter when the key is, a pattern and matches the ID database, if one key does not match then the system access will be denied. Speed reading time each reader reaches 0.2 seconds, but the reading time will be reduced if more complicated patterns are used.